Faktor Pengaruh Game Online Pada Remaja Di Desa Nangahale Kecamatan Talibura, Kabupaten Sikka - Ingkana; Ilmi Amilia Rahma (Hikamatzu | Journal of Multidisciplinary, 2024)
This research was conducted because of problems that occurred among teenagers in Nangahale Village, Kec. Talibura because of online games which make teenagers in Nangahale Village addicted to playing online games. Addiction to online games causes so many negative impacts that it causes harm to teenagers themselves, such as changes in their behavior. This research was conducted to determine the impact of online games. towards teenagers in Nangahale Village, Kec. Talibura, the causal factor that makes teenagers in Nangahale Village addicted to online games. The research method used is qualitative. The data sources used are primary and secondary data sources. Primary data sources were obtained from parents, RT heads and children. Secondary data sources were obtained from documents in the form of books, journals and mass media. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis technique used is data collection, data is collected and sorted, verified and draws conclusions. The results of research regarding the impact of online games on teenagers in Nangahale Village, District. Talibura influences behavioral patterns where teenagers become lazy in interacting with other people and the surrounding environment, and also affects their health due to lack of adequate rest time. Factors that influence Nangahale Village teenagers to become addicted to playing online games, technological developments, and lack of parental supervision. At adolescence, children are very curious/want to do things they have never done. Ways to overcome this include socialization and the need for parental supervision